Selection of biogas, solar, and wind power plants’ locations: An MCDA approach - Kheybari, Siamak; Mahdi Rezaie, Fariba (Journal of Supply Chain Management Science, 2020)
This study discusses a multi-criteria approach to locating biogas, solar and wind power plants that significantly addresses the challenge of global warming caused by power generation. Because the utility of locations to build renewable energy power plants depends on economic, social and environmental dimensions, after reviewing literature, the sustainable frameworks of criteria affecting the location of biogas, solar and wind power plants were examined in this paper. The offered frameworks are applied to determining the site of biogas, solar, and wind power plants in Iran. The provinces of Iran are assessed as alternatives in this paper. To compute the weight of criteria in the offered framework, data from a sample of experts in Iran are used via an online survey form designed based on the best-worst method (BWM). Using the results of the BWM and the performance data, the overall score are calculated for the various provinces of Iran. The results of this study indicate that energy saving, effect on resources and natural reserves and wind flow, respectively, are the most effective factors for determining the place of biogas, solar and wind power plants, and South Khorasan, Khuzestan, and Khuzestan show the best result for establishing biogas, solar, and wind power plants in Iran respectively.